Characteristics and Quality of Oleoresin Based On Different Stimulant Treatments - Alang, Anggi Nurhafizhah (Masyarakat Peneliti Kayu Indonesia, 2023)
AbstractThe quality of oleoresin determines the sale value of exports and imports. The quality of pine resin is determined by its color, moisture content, and impurities. The research method used a T-tes Independent to compare organic stimulants and sulfuric acid stimulants in tapping pine resin and referred to SNI 7837: 2016 to determine the quality of oleoresin. The results showed that trees treated with organic stimulants produced bright white oleoresin compared to trees treated with sulfuric acid stimulants which produced cloudy white oleoresin. However, both of them produce low levels of impurities and moisture content <5% so it is included in the super-premium quality class.